Wayang Potehi and the Resistance of the Chinese Ethnic Minority Group Against Racial Discrimination in Indonesia - Tayibnapis, Radita Gora; Kuswanti , Ana; Hapsari , Dian Tri (Journal of Ecohumanism, 2024)
Since the colonial era in Indonesia, the Chinese ethnic minority group has often experienced problems of racial discrimination in their lives. As a medium of resistance against racial discrimination, they utilize Wayang Potehi, Chinese glove puppets featured in stage performances. This qualitative research uses cultural identity theory and a critical ethnographic approach to find forms of racism and the implementation of Wayang Potehi as a resistance to racism. The results of this study show that the reason why the Chinese ethnic group uses Wayang Potehi by ignoring the truth of the knight figure is because in Java the Chinese ethnic group is a minority group that only relies on communication. Therefore, communication is built through the Wayang Potehi performance as a form of covert or symbolic resistance to the local community. In addition, the Chinese ethnic community also often experiences verbal violence in the form of insults or harassment.